A 7666-bp genomic deletion is frequent in Chinese Han deaf patients with non-syndromic enlarged vestibular aqueduct but without bi-allelic SLC26A4 mutations. Issue 12 (December 2015) - Pang, Xiuhong; Chai, Yongchuan; He, Longxia; Chen, Penghui; Wang, Xiaowen; Li, Lei; Jia, Huan; Wu, Hao; Yang, Tao
Abstract: Objectives: To investigate the genetic cause of the patients with non-syndromic enlarged vestibular aqueduct (EVA) but without bi-allelic SLC26A4 mutations. Methods: Presence of a homozygous genomic deletion was detected in a Chinese Han deaf patient (D1467-1) who failed to amplify the first three exons of SLC26A4 . The breakpoints of the deletion were fine-mapped and revealed by PCR amplification and sequencing. This deletion was subsequently screened in 22 Chinese Han EVA probands with mono-allelic SLC26A4 mutations. The possible founder effect of the newly identified genomic deletion was evaluated by haplotype analysis. Results: A homozygous c.-2071_307+3801del7666 deletion of SLC26A4 was identified in patient D1467-1. This novel genomic deletion was subsequently identified in 18% (4/22) of the Chinese Han EVA probands with mono-allelic SLC26A4 mutations. Haplotype analysis showed that this genomic deletion is likely a founder mutation in Chinese Hans. Conclusion: Our results suggested that the cryptic c.-2071_307+3801del7666 deletion of SLC26A4 is relatively frequent in Chinese Han non-syndromic EVA patients without bi-allelic SLC26A4 mutations. Screening of this genomic deletion should be incorporated into the routine DNA testing of SLC26A4 in Chinese Hans.